A CASE STUDY OF APPLYING FUZZY DEMATEL METHOD TO EVALUATE PERFORMANCE CRITERIA OF EMPLOYMENT SERVICE OUTREACH PROGRAM - Shieh, Jiunn-I; Chen, Hsuan-Kai; Wu, Hsin-Hung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
<span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 新細明體; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US">The economic and financial crisis leads to deterioration in the employment market in Taiwan. T<span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 新細明體; mso-font-kerning: 1.0pt; mso-ansi-language: EN; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN">he Bureau of Employment and Vocational Training, Council of Labor Affairs of Executive Yuan has been aggressively conducting Employment Service Outreach Program to resolve this tough issue. Under such program, the outreach personnel are recruited, trained, and supervised to perform the duties including identifying unemployed persons and then providing job information for them, using the social resource link to increase employment opportunities, conducting employer forum or workshops for job-seekers, and so on. This study applies fuzzy decision-making trial and evaluation laboratory method to not only <span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 新細明體; mso-font-kerning: 1.0pt; mso-ansi-language: EN; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN">evaluate the importance of the criteria but also construct the causal relationships among the criteria of evaluating outreach personnel. <span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 新細明體; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US">The results show that job-seeking service is the most critical criterion among the three first-tier criteria. In addition, identification of the number of unemployed people<span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 新細明體; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US"> and number of follow-up visit are the two most important causes under the category of job-seeking service when the performance of outreach personnel in Employment Service Outreach Program is evaluated.